Empathy and Alteration: The Ethical Relevance of a Phenomenological Species Concept. Issue 5 (13th September 2014) - Meacham, Darian
Abstract: The debate over the ethics of radically, technologically altering the capacities and traditional form of the human body is rife with appeals to and dismissals of the importance of the integrity of the human species. Species-integrist arguments can be found in authors as varied as Annas, Fukuyama, Habermas, and Agar. However, the ethical salience of species integrity is widely contested by authors such as Buchanan, Daniels, Fenton, and Juengst. This article proposes a Phenomenological approach to the question of species-integrity, arguing in favor of a phenomenon of species-recognition that carries an ethical pull. Building on Husserl's Phenomenological account of empathy and the lived-body, as well as Schopenhauer's concept of compassion as an ethical urphenomenon, I develop a "Phenomenological species concept" (PSC), which I argue has the ethical significance that biological species concepts do not. The PSC reorients the debate over human alteration and species integrity.